Highlights of recent IFPRI food policy research for USAID 2011: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2011)
In the wake of the food crises of the early 1970s and the resulting World Food Conference of 1974, a group of innovators realized that food security depends not only on crop production, but also on the policies that affect food systems, from farm to table. In 1975, the International Food Policy Research Institute (IFPRI) was founded. For the past 35 years, IFPRI has worked to provide solid research and evidence-based policy options to partners in donor and recipient countries. The issues have changed over time, going from food subsidies and commercialization of agriculture in the early years to country-led development, micronutrient malnutrition, and biosafety in the 2000s. Working with many longstanding partners, including the US Agency for International Development (USAID), IFPRI has produced food policy research that has contributed to reducing poverty and improving food security for the world's poor.